2015
DOI: 10.1007/s11199-015-0545-2
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Mothering: A Feminist Analysis of Frequent Work Travel and Independence in Families

Abstract: Competing cultural and gender expectations, especially aligned around paid and family work, make the contemporary experience of mothering difficult. The goal of this study is to illuminate, through the use of a feminist perspective, how families handle demands of paid and family work, along with the gendered nature of mothering, when mothers travel for work. Eighty-two mothers, fathers, and children from 22 U.S. families, in which mothers' jobs required frequent overnight travel, were interviewed to assess how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
(49 reference statements)
0
11
0
1
Order By: Relevance
“…Fulu and Miedema (2016) offer a theoretical review of the influence of globalized Islam on women in Muslim societies, as well as a detailed example of how this has been associated with an increase of IPV in recent years in the Maldives. Swenson and Zvonkovic (2016) used qualitative analysis to interpret the in-depth interviews they conducted with mothers, fathers, and children in 22 families, a rare example of incorporating the divergent perspectives of family members rather than having only one member speak for all.…”
Section: Methodological Pluralismmentioning
confidence: 99%
See 2 more Smart Citations
“…Fulu and Miedema (2016) offer a theoretical review of the influence of globalized Islam on women in Muslim societies, as well as a detailed example of how this has been associated with an increase of IPV in recent years in the Maldives. Swenson and Zvonkovic (2016) used qualitative analysis to interpret the in-depth interviews they conducted with mothers, fathers, and children in 22 families, a rare example of incorporating the divergent perspectives of family members rather than having only one member speak for all.…”
Section: Methodological Pluralismmentioning
confidence: 99%
“…Fulu and Miedema (2016) examine changes in intimate partner violence in the Maldives under the influence of globalization and globalized Islam. Swenson and Zvonkovic (2016) take an additional perspective by examining twoparent households and the perspectives of multiple family members. They incorporate the perspectives of mothers, fathers, and children to examine the relationship for family members when mothers travel for employment.…”
Section: Substantive and Theoretical Pluralismmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies point to women's greater risk of negative experiences traveling alone, others highlight the positives, especially for women's development (e.g., Bagnoli 2009;Heimtun 2012;Scopelliti and Giuliani 2004;Swenson and Zvonkovic 2016;Pung et al 2019;Yang et al 2018a). For example, research using diaries and interviews reporting travel experiences of 41 young adults found that many women reconstructed their identities as self-confident and free while adventure backpacking (Bagnoli 2009).…”
Section: Gender Patterns In Solo Travelmentioning
confidence: 99%
“…In a recent family study related to work travel (Swenson & Zvonkovic, in press), each family member was, in essence, a case with a distinctive vantage point, and his or her case was analytically elaborated while also using elements of his or her family situation as samples for variable‐oriented analyses and contrasts (e.g., each family member's perceptions of work travel as a case; families in which Dad travels, Mom travels, both travel, as variable‐oriented samples of families). Marsiglio and Roy () used interviews from several qualitative studies of fathers to consider possible family policy initiatives, but they also chose one or two case studies of individual fathers to reflect a more comprehensive and complex understanding of dimensions of fathering, such as personal meaning, kin work, or nurturant bonds with children.…”
Section: Data Quantity Size and Sampling Logic(s)mentioning
confidence: 99%